(untitled) (Boletin Médico de Postgrado, 2020)
Tumor lysis syndrome (TLS) is a potentially lethal complication due to massive release of nucleic acids, potassium and phosphate into the systemic circulation which is associated with severe hydroelectrolitic metabolic disorders. A retrospective review of clinical charts was performed in order to describe clinical characteristics of patients with possible TLS that were admitted to the Servicio de Medicina Interna of the Hospital General Universitario Dr. Luis Gómez López during the period 2017-2018. The results show that 50% of patients were between 51 and 70 years old and 65% were female. Breast cancer (29%), stomach cancer (15%) and Non-Hodgkin lymphoma (12%) were more frequent in patients with possible TLS. All patients showed at least three of the clinical features commonly associated with TLS such as nausea, vomiting, anorexia, weakness, cramps, hyperreflexia, oliguria, anuria, hematuria, hypotension, convulsion and dehydration. 46% of patients had hyperkalemia, 36% hypocalcemia and 18% hyperphosphatemia. Creatinine levels > 1,4 mg/dl were seen in 76% of patients. Definitive diagnosis of TLS was not possible in any of the patients included in this study due to the lack of laboratory studies required according to international guidelines.